Upregulation of AMPA receptor GluR2 (GluA2) subunits in subcortical ischemic vascular dementia is repressed in the presence of Alzheimer's disease - Mohamed, N; Zhao, Y; Lee, J; Tan, MG; Esiri, M; Wilcock, G; Smith, A; Wong, P; Chen, C; Lai, M (2011)
Glutamatergic AMPA receptors are of clinical significance in dementia because of their roles in mediating fast excitatory neurotransmission and other synaptic events relevant to cognition. Reductions in the AMPA receptor GluR2 subunit are well-established in Alzheimer's disease (AD), but the status of GluR2 in subcortical ischemic vascular dementia (SIVD) and mixed AD/SIVD (MIX) has not been investigated. In this study we measured GluR2 immunoreactivity and mRNA levels in the postmortem neocortex of a longitudinally assessed cohort of SIVD and MIX, together with age-matched controls. We found that GluR2 immunoreactivity and mRNA were up-regulated in SIVD, but remained unchanged in MIX. Furthermore, higher GluR2 immunoreactivity was associated with milder cognitive impairment and lower concentrations of Aβ42 peptide and phosphorylated tau. Our study suggests that GluR2 up-regulation may be an adaptive process in SIVD, and that this process is repressed in the presence of concomitant AD in mixed dementia. © 2011 Elsevier Ltd. All rights reserved.